Caracterização molecular da resistência aos carbapenêmicos e disseminação de amostras clínicas e ambientais de Acinetobacter baumannii multirresistentes produtoras de biofilme: caracterização molecular de Acinetobacter baumannii - Royer, Sabrina (2017)
The emergence of infections associated with new antimicrobial-resistant Acinetobacter baumannii genotypes represents a major challenge. Thus, the detection and knowledge of its epidemiological and molecular characteristics have fundamental importance for the development of treatment, prevention, and control strategies. This study aimed to determinate the diversity of resistance mechanisms, to evaluate the biofilm production through phenotypic techniques and scanning electron microscopy (SEM), and to investigate the clonal dissemination and the predominant Sequence Types (STs) in multiresistant strains of A. baumannii from clinical (tracheal aspirate, n=17) and environmental (surface, n=6) origin, isolated at the Adult Intensive Care Unit (ICU) of the Clinical Hospital of the Federal University of Uberlândia (HC-UFU). Additionally, one clinical (clone A) and one environmental (clone H) strain had their complete genome sequenced with partial analysis of their resistomes. All strains were submitted to polymerase chain reaction (PCR) for the detection of ISAba/ genes and their association or not with oxacillinases (OXA-51 and OXA-23), genes of outer membrane proteins (OMPs) carO and pme33-36, and genes encoding AdeABC (adeB), AdeFGH (adeG) and AdeIJK (adeJ) efflux pumps. Confirmation of tigecycline and carbapenem resistance was done by the Etest®. Most of the strains were characterized as extensively drug-resistant (XDR) with very high minimal inhibitory concentrations (MICs) for tigecycline and carbapenems. The association of ISAba//OXA-51, ISAba//OXA-23 and the presences of carO and pme 33-36 were observed in 91.3%, 52.2%, 82.6% and 100% of the strains, respectively. The genes adeB, adeG and adeJ were observed in all strains analyzed. The consumption of Imipenem, Meropenem, Tigecycline and Polymyxin B/Colistin (DDD/1000 patients-day) was also evaluated in the period from January 2011 to December 2012. Changes in the consumption of these antimicrobials were observed during the period investigated. According to clonal profiles obtained by the Pulsed Field Gel Electrophoresis (PFGE) technique, ten A. baumannii strains were selected for analysis by real-time PCR (qPCR), phenotypic analysis of biofilm production and Multilocus Sequence Typing (MLST). Only adeB gene was considered hyper-expressed. MLST results demonstrated polyclonal dissemination, identifying eight STs and five clonal complexes (CCs), with predominance of CCs 113, 229 and 109. All A. baumannii evaluated strains adhered to the unmodified polystyrene surface and produced biofilm, with no significant difference between clinical and environmental isolates. SEM images confirmed the ability of adhesion and the presence of a visible extracellular matrix. Our study found a wide variety of clonal complexes related to XDR A. baumannii carrying the b/aOXA_23 gene frequently associated with ISAba/ (Tn2008) as the main mechanism of carbapenems resistance, in addition to the over expression of the AdeABC efflux pump. The understanding of the mechanisms of resistance and the pathogenic potential of this microorganism helps to explain its persistence in the hospital environment and can provide tools to improve the treatment of serious infections, as well as, the measures of control and prevention of these infections.